Dark Personality: Adaptation of the Short Dark Tetrad (SD4) Measurement Tool - Muhammad Ardi, Ardi; Aripuspita, Bella Anneeshea; Edwiansyah, Nur Chairul; Yusron, Isman Rahmani; Nitiharja, Dirga Atmaka (Analitika: Jurnal Magister Psikologi UMA, 2025)
This study aimed to adapt the Short Dark Tetrad (SD4) instrument into Indonesian and evaluate its construct relevance and internal consistency. The SD4, which measures Machiavellianism, narcissism, psychopathy, and sadism, is an important tool for understanding dark personality traits. The adaptation was guided by the conceptual framework of Paulus et al. Data were collected through an online platform provided by PT Nirmala Satya Development (NSD), and model fit, and item performance were examined. The results indicated that the model demonstrated acceptable fit, with RMSEA, SRMR, and GFI values falling within appropriate ranges, although CFI and TLI values were slightly below the ideal thresholds. Internal consistency was strong, with reliability coefficients suggesting the instrument measured the intended traits reliably. Most items showed adequate representation of their respective dimensions. These findings support the use of the Indonesian version of SD4 in personality research. However, further research is recommended to refine the model and examine its applicability across different populations and cultural contexts.